Model-view-controller approach for e-Zakah - Ah. Fathonih; Dian Sa’adillah Maylawati; Muhammad Ali Ramdhani (Institute of Advanced Engineering and Science, 2019)
Zakah (alms) has a strategic position in terms of Islamic value and terms of the development of the welfare of the people. In the current digital era, the use of technology can facilitate zakah worship more easily, quickly, efficiently, and secure. This study aims to analyze and design electronic zakah (e-Zakah) structurally and systematically using the Model-View-Controller (MVC) approach. MVC is an approach or pattern of object-oriented analysis and design for software development that widely used today. MVC is implemented in the analysis and design modelling using Unified Modeling Language (UML) for e-Zakah. Based on the traceability result of analysis and design of e-Zakah, it can be concluded that the e-Zakah analysis and design model has been met all of zakah concept, user and software requirements, and all of models can be traced to each other. Therefore, e-Zakah analysis and design model in this study is ready to be built as a software.